THE INFLUENCE OF SELF-ADJUSTMENT AND SOCIAL SUPPORT ON HARDINESS IN OUT-OF-TOWN STUDENTS - Fedha, Shafa; Ansyah, Eko Hardi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aimed to investigate the effect of self-adjustment and social support on the hardiness of out-of-town (overseas) students, who often encounter psychological challenges stemming from differences in lifestyle, language, and social norms in their new environment. Method: Employing a quantitative research design, data were collected from 204 overseas students using standardized questionnaires. Hypothesis testing was conducted through multiple linear regression analysis using SPSS 29 for Windows. Results: The findings revealed a significant simultaneous effect of self-adjustment and social support on hardiness, indicated by an F-value of 24.828 and a significance level of 0.001 (p < 0.05). The model accounted for 19.8% of the variance in hardiness, suggesting that the remaining 80.2% is explained by other unexamined variables. Novelty: This study contributes to the psychological literature by highlighting the joint predictive power of self-adjustment and social support in fostering resilience among overseas students, emphasizing the need for targeted interventions that strengthen these factors to support student well-being in cross-cultural academic settings.